(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
The word Nighantu in Ayurveda implies the group of drugs, synonyms, properties and their description of part used. Ayurveda treatment possesses herbal, mineral, animal origin products which mainly take part in the treatment of various health ailments. Dhanvantari Nighantu is one of them and is oldest Ayurvedic materia medica placed between 8th -10th AD. The original name of this lexicon is Drvayavali Samucchaya. This book contains seven Vargas namely; Guduchadi Varga, Shatapushpadi Varga, Chandanadi Varga, Karaviradi Varga, Amradi Varga, Suvarnadi Varga, and Mishrakadi Varga, and the total numbers of drugs are 527. The drugs are classified in this book are on the basis of Rasa, Guna, Virya, Vipaka etc. The Nighantu starts with salutation to Lord Dhanvantari, then the author go on narrating the synonyms and properties of the drugs. The peculiar of this Nighantu is the Varga starts with the name of the first drug e.g, Guduchi as Guduchadi Varga. And the Vargas of the medicinal plant are explained systematically first with synonyms and then properties. Also Dadima and Kadali are not mentioned under Phala Varga but in Shatapushpadi Varga and Karaveeradi Varga respectively. The present literary study reveals the critical analysis of the text and the drugs, their properties. Further scope of study is remove the controversy of the date, plants on the basic of literature survey, gathering information by the local people, proper inspection with the microscopes, Sparsha (by touching) and compare with modern flora and fauna with taxonomical parameters.